Service Quality Analysis in Retail Industry using Servqual and Kano Model - Nur Rahmawati; Dwi Sukma Donoriyanto (Future Science)
In the retail industry, service quality is the main consideration and the quality and completeness of the products offered. The recent conditions that result in declining sales turnover at most of the retail industries in Surabaya prompted this research to be carried out. In this study, an analysis of the service quality in one of the retail industries in Surabaya will be carried out. The method used is the integration between servqual and Kano models. Both methods are used because they are proven to show good results in previous research. The results obtained from this study are that several service attributes need to be improved because of the negative satisfactions value result. Those attributes are the availability of items location instruction. Item price should be matched with the price tag, standard pricing, safety parking, safety shopping, good salesperson, and careful cashier.